EXPERIENCES AND LIFE IN THE PAN AMERICAN GAMES - RIO 2007 (Fiep Bulletin - online, 2014)
This study presents an experience report as a volunteer in the Pan American Games held in the city of Rio de Janeiro in July, 2007 from the enrollment to the participation in the related games, accreditation, accomplished work on transit and transportation area as a support navigator, organization, among other works. It presents expectations of the Work Force organization committee for achievement and expected results of the Pan American games, as well as procedures and responsibilities during the games. It ponders the importance of knowing at least one foreign language for better communication during the event, life and experience accomplished during this daily contact and knowing the relevant aspect of the Pan American Village.
Keywords: Pan American Games; Volunteer; Experience